Growth and Optical, Mechanical, Electrical Behaviour of Zinc Formate Dihydrate Single Crystal: A Third Order Nonlinear Optical Material. (2019) - Chinnasamy, E.; Indumathi, N.; Deepa, K.; Madhavan, J.; Senthil, S.
Abstract: Optically good quality single crystals of Zinc Formate Dihydrate (ZFD) were grown by slow evaporation technique. The grown crystals were characterized by various characterization techniques such as single crystal XRD, FT-IR, UV-Vis, dielectric, microhardness and Z-scan studies. The monoclinic crystal system of the grown crystal was confirmed by Single crystal X-ray Diffraction analysis. The functional groups present in the crystal were identified by FT-IR analysis. The transparency of the crystal was identified using UV-Vis spectral studies. Dielectric studies were measured for the crystal from 50 Hz to 5 MHz at room temperature. Mechanical behaviour of the crystal was measured using Vickers microhardness tester and this study confirms that the grown crystal belongs to soft material category. The nonlinear absorption coefficient (β), nonlinear refractive index (n2 ) and third harmonic generation studies were also carried out for the title crystal.